PENATALAKSANAAN HOLISTIK PENYAKIT EPILEPSI PADA PASIEN REMAJA DENGAN TINGKAT PENGETAHUAN YANG MINIMAL MELALUI PENDEKATAN KEDOKTERAN KELUARGA - Riska Priyani; Cindy Gustavia Dwirusma; Diana Mayasari (CV. Jasa Sukses Abadi, 2023)
In developing countries, the incidence of epilepsy is 61-124/100,000 children per year. The prevalence of epilepsy cases in Indonesia is 8.2 per 1,000 population with an incidence rate of 50 per 100,000 population. In the management of epilepsy patients, cooperation from various parties is needed, one of which is the role of family doctors. Identify internal, external risk factors and clinical problems found in patients, apply a holistic and comprehensive family doctor approach according to the problems found in patients, and carry out evidence-based medicine management that is family-approach, patient-centered and community oriented. The study is a case report. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from the patient's medical record. Assessment was qualitatively and quantitatively carried out based on the initial holistic diagnosis, process, and end of the visit using food recall. A male patient, 17 years old, came to take an epilepsy control referral letter to the hospital. The patient has been diagnosed with epilepsy since 7 years ago. Patients routinely take medication to the hospital every month. At this time the patient said that the seizures began to decrease after taking the drug every day. Enforcement of diagnosis and management of these patients has been done holistically, patient centered, family approach and community oriented based on several theories and the latest research. In the process of behavior change, the patient has reached the trial stage